Exploring the Effectiveness of two Scales for Measuring Cultural Intelligence of the Preparatory School Students (Journal of the College of Education for Women, 2019)
The present study aims at exploring tow cultural intelligence scales of preparatory school students. It also aims at finding out the statistically significant differences according to gender and specification. Accordingly, the present study seeks to answer the following questions:Is there cultural intelligence of the preparatory school students?Is there any statistically significant differences according to gender and specification variables?Is there a scale more effective than cultural intelligence scales?The stratified random sampling method is used to for selecting the sample of (216) students of scientific and humanistic specifications from Al Karkh sector (first-second –third) preparatory schools.Two cultural intelligence scales have been adopted as a study instrument. The first scale is off (Al Janaby, 2017) and the second one is of (Aeidy, 2010). The reliability and validity of the two scales have been ensured.The SPSS has been used to show the following results:There is cultural intelligence of the preparatory school students.There are statistically significant differences according to gender variable in favor of the females in (Al Janaby, 2017) scale and there are no differences in (Aeidy, 2010) scale.There are no differences according to specification variable in (Al Janabys, 2017) scale, while the differences are statistically significant in (Aeidys, 2010) scale.The two scales have high construct validity and reliability. Accordingly, the researcher has got several recommendations and suggestions.Keyword: School, Students, Scale.